1994
DOI: 10.1079/bjn19940075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dose and modification of viscous properties of oat gum on plasma glucose and insulin following an oral glucose load

Abstract: An extract from oats known as oat gum (OG) is composed mainly of the polysaccharide (1 + 3) (1 + 4)-/?--D-glucan, which is highly viscous in aqueous solution. Viscous polysaccharides are known to attenuate postprandial plasma glucose and insulin responses. The purposes of this study were to determine the doseresponse to OG and establish quantitatively the effect of viscosity on plasma glucose and insulin levels of healthy humans consuming 50 g glucose. Increasing the dose of OG successively reduced the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
194
0
6

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(208 citation statements)
references
References 15 publications
8
194
0
6
Order By: Relevance
“…It has been shown that it is the soluble, viscous fibers that reduce the rate of absorption, flatten the postprandial glycemia and lower cholesterol levels (Landin et al, 1992;Anderson et al, 1990;Groop et al, 1993;Würsch and Pi-Sunyer, 1997;Chandalia et al, 2000). The viscosity of the fiber relates positively to the degree of flattening of postprandial glycemia (Tappy et al, 1996;Wood et al, 1994;Jenkins et al, 1978). The form in which the fiber is ingested is important.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that it is the soluble, viscous fibers that reduce the rate of absorption, flatten the postprandial glycemia and lower cholesterol levels (Landin et al, 1992;Anderson et al, 1990;Groop et al, 1993;Würsch and Pi-Sunyer, 1997;Chandalia et al, 2000). The viscosity of the fiber relates positively to the degree of flattening of postprandial glycemia (Tappy et al, 1996;Wood et al, 1994;Jenkins et al, 1978). The form in which the fiber is ingested is important.…”
Section: Discussionmentioning
confidence: 99%
“…The soluble fiber in oat, b-glucan, has been reported to modify the postprandial blood glucose responses by delaying the carbohydrate absorption (Anderson et al, 1990;Wood et al, 1994;Behall et al, 1998;Battilana et al, 2001). In addition to stabilizing glycemic responses, other positive health effects have been attributed to the b-glucans, including reduced plasma total and low-density lipoprotein (LDL)-cholesterol, weight management and improved gastrointestinal function.…”
Section: Introductionmentioning
confidence: 99%
“…The role of viscosity of b-glucan in reducing the postprandial blood glucose levels is well documented in experimental studies (Wood et al, 1990(Wood et al, , 1994(Wood et al, , 2000Braaten et al, 1991;Bourdon et al, 1999). Wood et al (1994) used increasing doses of pure and totally dissolved oat b-glucan to show that the oat gum decreases postprandial glucose and insulin responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wood et al [27], showed that the viscosity of β-glucans accounted for 79%-96% of the changes in postprandial glucose and insulin response following the ingestion of a 50 g glucose drink. In addition to the concentration and total amount of b-glucans in food, the hypoglycemic effects of β-glucans resulting from their viscosity is suggested to be controlled by their solubility and molecular weight [15].…”
Section: Thermal Propertiesmentioning
confidence: 99%